Serum Albumin And C-reactive Protein as Prognostic Biomarkers in Hospitalised Patients with Community Acquired Pneumonia - V., Latha; S., Nagaraj; Ahmed T. M., Tanvir; P., Ramurthy (International Journal of Innovative Research in Medical Science, 2022)
Background: Pneumonia is an infection of the pulmonary parenchyma, causing significant morbidity and mortality. Inflammation potentiates hypoalbuminemia. CRP is an acute phase reactant produced by the liver in response to inflammation, which depends on severity of illness. Serum albumin concentration as a negative acute phase reactant, changes with change in CRP(C-reactive protein) value. Objectives: To study the prognostic significance of commonly used biomarkers serum Albumin level and C - reactive protein in hospitalized patients with Community Acquired Pneumonia. Methodology: The prospective study was conducted in a hospital affiliated to Vijayanagara Institute of Medical Science, Ballari. Patients with signs and symptoms of CAP were hospitalized based on a CURB-65 score. After informed consent, all relevant data was collected. Clinical examination and laboratory parameters i.e. Serum albumin & C - reactive protein levels on day 1, 3 & 7/discharge were carried out. The values of serum albumin & C - reactive protein were analyzed with the clinical profile and outcome in these study groups. Results: In our study, CAP was more commonly seen among the age group of 61-70 yrs (27%). COPD was a major associated co-morbidity (50%) and smoking was an important risk factor (70%). The majority had a CURB 65 score of >3-5 on admission (64%). Out of 50 patients, 26% of them had severe hypoalbuminemia (<2.5 mg/dl) and 58% of them had mild hypoalbuminemia (2.5-3.5 mg/dl) on day 1 of admission. When serum albumin levels at the time of admission were analyzed for the time of discharge, there was significant change (P=0.025) noted, i.e an increase in serum albumin levels were seen in all patients who had clinical signs of resolution. 38% of patients had serum CRP levels <100 mg/l and 40 % had 101-200 mg/l and 22% of them had levels > 200 mg/l. There was decrease in CRP level at the time of discharge (p=0.001). Serum Albumin levels and CRP levels showed significant change from day 1 to the day of discharge (p=0.025 and P=<0.001) respectively. ICU requirement, need for mechanical ventilation and other outcomes correlated well with serum albumin levels (p=0.021, p=0.004, p=0.003 respectively). Conclusion: Our study showed a history of smoking, COPD and hypoalbuminemia at presentation were major risk factors present for CAP. Patients with severe hypoalbuminemia had high morbidity and mortality in the form of ICU requirement, need for mechanical ventilation, complications and death. CRP serves as an important marker of inflammation whose series levels reduce significantly with cure / resolution of pneumonia. Thus, serum albumin levels and C reactive protein can be used as a prognostic biomarker in community acquired pneumonia.